Prostate Cancer Survival and Mortality according to a 13-year retrospective cohort study in Brazil: Competing-Risk Analysis - Sonia Faria Mendes Braga; Rumenick Pereira da Silva; Augusto Afonso Guerra Junior; Mariangela Leal Cherchiglia (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2021)
ABSTRACT: Objective: To analyze cancer-specific mortality (CSM) and other-cause mortality (OCM) among patients with prostate cancer that initiated treatment in the Brazilian Unified Health System (SUS), between 2002 and 2010, in Brazil. Methods: Retrospective observational study that used the National Oncological Database, which was developed by record-linkage techniques used to integrate data from SUS Information Systems, namely: Outpatient (SIA-SUS), Hospital (SIH-SUS), and Mortality (SIM-SUS). Cancer-specific and other-cause survival probabilities were estimated by the time elapsed between the date of the first treatment until the patients' deaths or the end of the study, from 2002 until 2015. The Fine-Gray model for competing risk was used to estimate factors associated with patients' risk of death. Results: Of the 112,856 studied patients, the average age was 70.5 years, 21% died due to prostate cancer, and 25% due to other causes. Specific survival in 160 months was 75%, and other-cause survival was 67%. For CSM, the main factors associated with patients' risk of death were: stage IV (AHR = 2.91; 95%CI 2.73 - 3.11), systemic treatment (AHR = 2.10; 95%CI 2.00 - 2.22), and combined surgery (AHR = 2.30, 95%CI 2.18 - 2.42). As for OCM, the main factors associated with patients' risk of death were age and comorbidities. Conclusion: The analyzed patients with prostate cancer were older and died mainly from other causes, probably due to the presence of comorbidities associated with the tumor.